THE DYNAMICS OF GENDER EQUALITY AND NEW DIRECTIONS FOR THE ROLE OF SAUDI WOMEN - Akhmad Saikuddin; Abdul Karim Amrullah (Arabic Literature Department, 2023)
This study explores the dynamics of gender equality between men and women in Saudi under the shadow of a patriarchal social structure and ultra-conservative Wahhabi theology. This study will also explore the views of Asghar Ali Engineer regarding the status of women in Islam through liberation theology and how it is contextualized with the status and role of Saudi women today. This research is a qualitative research whose database is literature in the form of authoritative books, journals and web articles. The results of this study are that gender equality between men and women in Saudi is experiencing dynamics that continue to change according to social conditions and interests that occur in the country. In decades Saudi women have experienced very strict restrictions, their role is limited to the domestic sphere and very few Saudi women have a role in the public sphere. Seeing this condition of Saudi women, Asghar Ali Engineer through liberation theology wants to remove all forms of subordination experienced by women, and Asghar Ali Engineer's view of liberation theology finds its relevance to Saudi women today where they are now enjoying their freedom and their rights have been restored.